2016
DOI: 10.1002/pro.2968
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into SAM domain‐mediated tankyrase oligomerization

Abstract: Tankyrase 1 (TNKS1; a.k.a. ARTD5) and tankyrase 2 (TNKS2; a.k.a ARTD6) are highly homologous poly(ADP-ribose) polymerases (PARPs) that function in a wide variety of cellular processes including Wnt signaling, Src signaling, Akt signaling, Glut4 vesicle translocation, telomere length regulation, and centriole and spindle pole maturation. Tankyrase proteins include a sterile alpha motif (SAM) domain that undergoes oligomerization in vitro and in vivo. However, the SAM domains of TNKS1 and TNKS2 have not been str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…Both TNKS and TNKS2 polymerize through their SAM domains (De Rycker and Price, ; Mariotti et al, ; Riccio et al, ). Recent crystallographic studies of the SAM domains revealed the primarily electrostatic nature of the head‐to‐tail SAM–SAM interfaces within the helical filament (Mariotti et al, ; Riccio et al, ) (Figure F), in agreement with a polymer model guided by NMR studies to identify the residues perturbed upon polymerization (DaRosa et al, ). Compatible with the outward‐facing N‐ and C‐termini in the filament (DaRosa et al, ; Mariotti et al, ; Riccio et al, ), full‐length tankyrase indeed polymerizes (De Rycker and Price, ; Mariotti et al, ; Riccio et al, ).…”
Section: Tankyrase As a Scaffold In Wnt/β‐catenin Signalling – A Strusupporting
confidence: 59%
See 2 more Smart Citations
“…Both TNKS and TNKS2 polymerize through their SAM domains (De Rycker and Price, ; Mariotti et al, ; Riccio et al, ). Recent crystallographic studies of the SAM domains revealed the primarily electrostatic nature of the head‐to‐tail SAM–SAM interfaces within the helical filament (Mariotti et al, ; Riccio et al, ) (Figure F), in agreement with a polymer model guided by NMR studies to identify the residues perturbed upon polymerization (DaRosa et al, ). Compatible with the outward‐facing N‐ and C‐termini in the filament (DaRosa et al, ; Mariotti et al, ; Riccio et al, ), full‐length tankyrase indeed polymerizes (De Rycker and Price, ; Mariotti et al, ; Riccio et al, ).…”
Section: Tankyrase As a Scaffold In Wnt/β‐catenin Signalling – A Strusupporting
confidence: 59%
“…Recent crystallographic studies of the SAM domains revealed the primarily electrostatic nature of the head‐to‐tail SAM–SAM interfaces within the helical filament (Mariotti et al, ; Riccio et al, ) (Figure F), in agreement with a polymer model guided by NMR studies to identify the residues perturbed upon polymerization (DaRosa et al, ). Compatible with the outward‐facing N‐ and C‐termini in the filament (DaRosa et al, ; Mariotti et al, ; Riccio et al, ), full‐length tankyrase indeed polymerizes (De Rycker and Price, ; Mariotti et al, ; Riccio et al, ). TNKS and TNKS2 form cytoplasmic puncta rather than microscopically visible filaments, which may reflect the dynamic nature of the polymers (Mariotti et al, ; Riccio et al, ).…”
Section: Tankyrase As a Scaffold In Wnt/β‐catenin Signalling – A Strusupporting
confidence: 59%
See 1 more Smart Citation
“…(A)]. Immediately upstream of this catalytic domain lies a SAM domain responsible for TNKSs polymerization . The extreme N‐terminal end harbors a histidine, serine, proline‐rich segment (a region lacking in tankyrase‐2), followed by a large ankyrin repeat domain composed of five conserved subdomains or ankyrin repeat clusters (ARCs) connected by conserved linkers.…”
Section: Introductionmentioning
confidence: 99%
“…Immediately upstream of this catalytic domain lies a SAM domain responsible for TNKSs polymerization. [21][22][23][24][25][26] The extreme Nterminal end harbors a histidine, serine, proline-rich segment (a region lacking in tankyrase-2), followed by a large ankyrin repeat domain composed of five conserved subdomains or ankyrin repeat clusters (ARCs) connected by conserved linkers. With the exception of ARC3, each ARC has a highly conserved binding groove that can recognize a tankyrasebinding motif (TBM) having the form: RXXUDG where X is any amino acid, and U is a small hydrophobic amino acid (Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 99%